Effect of process parameters on machinability characteristics of CO2 laser process used for cutting SS-304 Stainless steels. (2019) - Rajesh, K.; Murali Krishnam Raju, V.V.; Rajesh, S.; Sudheer Kumar Varma, N.
Abstract: This project defines there occurs a change in mathematical values of surface roughness (Ra, μm) and Kerf width (Kw, mm), while conducting experimentation of CO2 laser cutting on SS-304 Stainless steel using Nitrogen as assistance gas. The laser kerf width and cut edges quality was influenced by the process parameters like cutting speed ( V ), Assist gas pressure ( p ) laser power ( P ). The experiment was constructed and followed on the base of L27 orthogonal array. A predictive model is generated by using multiple regression analysis through ANOVA and implemented to find relative influence of process parameters on Kw and Ra.